PENYELENGGARAAN ASSESMEN BAGI NARAPIDANA TERORIS DITINJAU DARI KEPUTUSAN DIRJEN PEMASYARAKATAN KEMENKUMHAM RI - JATI, AZZAH ALMARORO (Journal of Correctional Studies, 2024)
Assessment is a process of collecting information using appropriate tools and techniques. Assessment is used to determine the risk of recidivism and to map the rehabilitation needs of terrorist inmates (Napiter). This research aims to understand the implementation of assessments carried out by correctional officers for terrorist inmates. This study uses a normative legal method with secondary data sources in the form of primary legal materials, specifically the Decree of the Director General of Corrections of the Ministry of Law and Human Rights of the Republic of Indonesia, collected through a literature review. The results of this research show that the assessment process is carried out using various instruments, namely, instruments for assessing criminogenic factors of terrorist inmates and instruments for assessing the rehabilitation needs of high-risk terrorist inmate categories.